Towards An Analysis of Rural Consumers Brand Awareness in Rural Markets in Indian Scenario: Exploring Strategies to Promote Brand Awareness in Rural Indian Markets (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In the marketing development implementation, rural markets are increasingly gaining a lot of status of important in the marketing planning exercise by the consumer and social dealers. Rural marketing includes rigorous personal selling determinations in comparison to metropolitan marketing. To efficiently knock the rural market a trader must link it to the activities undertaken by rural the population. Also, it can be used in huge numbers to enable association of the brand with the innumerable ceremonies, merriments, commemorations, fairs to attract rural get-togethers.All around the globe India has the greatest ability for serving the rural market. Such markets are price perceptive and are related to the level of local income. An effort is carried out to encourage the promotion of brand image in the rural markets. They are recognizing the unit in which rural populations are in an improved situation with a higher per capita income level. This is possibly achieved by using the different rural traditional media for tapping the untapped potential for reaching out to rural areas by using local languages. Rural India institutes in the foundation of our country and contributes towards producing higher than almost half of the national income.